2002
DOI: 10.1038/sj.ejhg.5200823
|View full text |Cite
|
Sign up to set email alerts
|

WFS1 mutations in Spanish patients with diabetes mellitus and deafness

Abstract: Wolfram syndrome (WS) is an autosomal recessive neurodegenerative disorder characterised by early onset diabetes mellitus and progressive optic atrophy, as well as other clinical features such as deafness, diabetes insipida, renal tract abnormalities and diverse psychiatric illnesses. A gene responsible for WS was identified in 4p16.1 (WFS1). It encodes a putative 890 amino acid transmembrane protein expressed in a wide spectrum of tissues. Recently, a new locus for WS has been located on 4q22-24, providing ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 14 publications
2
23
1
Order By: Relevance
“…In this animal model, beta cell death occurred by an accelerated process of apoptosis; similarly, increased levels of markers reflecting ER stress were also demonstrated [7][8][9]. In line with the outcome of studies in mice, previous and statistically undersized human studies have indicated that variation in WFS1 may be associated with type 1 diabetes mellitus [10], type 2 diabetes mellitus [11] and a combination of diabetes mellitus and deafness [12,13]. Moreover, two patients with the Wolfram syndrome were reported to be without insulin-producing beta cells [14].…”
supporting
confidence: 78%
See 1 more Smart Citation
“…In this animal model, beta cell death occurred by an accelerated process of apoptosis; similarly, increased levels of markers reflecting ER stress were also demonstrated [7][8][9]. In line with the outcome of studies in mice, previous and statistically undersized human studies have indicated that variation in WFS1 may be associated with type 1 diabetes mellitus [10], type 2 diabetes mellitus [11] and a combination of diabetes mellitus and deafness [12,13]. Moreover, two patients with the Wolfram syndrome were reported to be without insulin-producing beta cells [14].…”
supporting
confidence: 78%
“…6.5% (95% CI [0. 8,12.1] increase per allele, p=0.025). Similar results were observed for 30 min serum insulin and Cpeptide after an oral glucose load (ESM Table 2).…”
Section: Resultsmentioning
confidence: 95%
“…77 An additional locus for WS has been identi¢ed at Ch.4q22-24, suggesting the syndrome is genetically heterogeneous. 78 …”
Section: Hypothalamic Diabetes Insipidusmentioning
confidence: 99%
“…It has been postulated to be a transmembrane endoglycosidase protein, mainly localized in the endoplasmic reticulum and involved in membrane trafficking, protein processing, and/or in the anti-apoptotic machinery for the survival of islet beta-cells [Gerbitz, 1999]. So far, more than 60 different causative molecular defects and 30 neutral polymorphisms in the WFS1 gene have been reported, most of which are private mutations [Domenech et al, 2002;Gomez-Zaera et al, 2001;Khanim et al, 2001;Tessa et al, 2001]. Among the inactivating changes, the most prevalent are frameshift alterations (40% of total) and missense changes (35%), followed by nonsense mutations (21%).…”
Section: Introductionmentioning
confidence: 99%